REKONSTRUKSI PERAN DAN FUNGSI MASJID SEBAGAI PUSAT KEGIATAN PENDIDIKAN ISLAM - Mulyono Mulyono (MUADDIB Jurnal Kependidikan dan Keislaman, 2017)
Rasulullah SAW has given the role in the effort to create the ability of Muslims to become kholifah on earth and devoted servant of Allah SWT by doing Islamic education to the companions in the mosque. This tradition is followed by the followers of Islam and the subsequent Islamic rulers, even in the development of Islamic scholars the process of "ta'lim" more often done in the mosque, this tradition is known as "halaqah", many scholars who were born from halaqah tradition. The main learning method is rote, then in language learning by imitating ustadz utter assisted by guide. Islamic education in this mosque continues to grow until the end of the third century hijriyah. After that time the transition of scholarly learning center took place from mosque, then khan mosque, and new to madrasah as result of influence of scientific development and society requirement about educational institution. Some of the reasons for Islamic education have turned to madrasahs because: (1) educational activities in the mosque are considered to have disrupted the main function of the institution as a place of worship; (2) the development of scientific needs as a result of the development of science; And (3) the emergence of a new orientation in the implementation of education, ustadz need to earn income for the sake of survival and it is not possible in the mosque, then the madrasah was built. Thought is also a consideration for the management of mosques in Indonesia. The mosque is more just to run the worship mahdhoh, not serve the ummah for 24 hours, after the use of prayers in congregation locked mosques, even in some areas of the mosque used for ceremonial rituals that sometimes do not comply with Islamic teachings. As a result the mosque abandoned its congregation. Some studies show that if the mosque is properly introduced to Muslims, it is functioned as a place to run the mahdhoh worship as well as the center of Islamic education and solve community problems proved to be quite effective. Therefore, it is necessary to reconstruct the role and function of the mosque as the center of Islamic education. Some efforts that need to be done include: (1) the need to mobilize the ta'lim assembly within the mosque; (2) empower teenagers into youth containers of mosques; (3) organizing various types of training and seminars; (4) making the mosque a center of knowledge; (5) enhance cooperation with government and society; (6) empowering the poor who are the mosque's responsibility; And (7) fostering the independence of the mosque.